PENERAPAN PENDEKATAN PEMBELAJARAN OPEN ENDED DAN PROBLEM POSING DENGAN MEDIA POHON MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR - Azin Taufik (Jurnal Pendidikan Matematika (JPM), 2015)
Based on interviews and observations which did by researcher before doing research obtained information that creative thinking ability and students learning result of class X A of MAN Malang II Batu City still relatively low, it is because in teaching the teacher only give the procedure a matter without explaining what the procedures used. This research aims to know whether the open ended approach and problem posing with mathematical tree media can improve the creative thinking ability and learning result the trigonometry of students X A Man Malang II Batu City. Based on research which has been done found the following matters: (1) creative thinking ability of students in the cycle I classified as creative is the percentage of success is 67.85% while in the cycle II increased with the percentage of success is 78.57% classified as very creative;(2) completeness of students learning result in the cycle I still was reached 50.00% with students who completed study are 14 students and who did not complete study are 14 students with class average 63.25, while in the cycle II was reached 89.28% with students who completed study are 25 students and who did not complete study are 3 students with class average 80.46; (3)management open ended learning approach and problem posing with mathematical tree media in the cycle I was reached 88% classified as the criteria very good and in the cycle II was reached 100% classified as the criteria very good it is shown by the implementation all indicators and descriptors open ended learning approach and problem posing with mathematical tree media are very good; and (4) students activities in the learning using open ended learning approach and problem posing with mathematical tree media in the cycle I was reached 82.50% classified as very good and more enhanced again in the cycle II up to 100% classified as the criteria very good, it is shown with the students who had dared to asking about something which have not understood, the students dared to expressed their opinion in making the questions and answer through mathematical tree media, the students dare to presented the result of their work in front of the class.